Spectral TRIP enables ductile 1.1 GPa martensite. (1st June 2016) - Wang, M.-M.; Tasan, C.C.; Ponge, D.; Raabe, D.
Abstract: Introduction of interlath reverted austenite is an effective method to design ductile lath martensitic steels. The challenge in this concept is that all reverted austenite films have similar mechanical stability, hence, they all undergo transformation-induced plasticity (TRIP) at the same strain level. Here we propose a new thermo-mechanical treatment route to activate the TRIP effect over a broad strain regime and refer to it as 'spectral TRIP effect'. It aims at spreading the micro-mechanical stability of reverted austenite grains by widening the austenite nucleation barrier in martensite. To validate the proposed thermo-mechanical treatment route, an as-quenched medium-Mn martensitic steel was cold rolled prior to the reversion treatment at 600 °C. Microstructure characterization was carried out by electron backscatter diffraction (EBSD) and electron channeling contrast imaging (ECCI). Mechanical tests show that the approach is effective. The spectral TRIP effect improves both, the strength and the ductility due to the well dispersed size distribution and the associated size-dependent deformation and phase transformation behavior of the reverted austenite grains, extending TRIP-related work hardening over a broad strain range. Graphical abstract: